Prevention of Bacterial Infection in Biliary and Pancreatic Endoscopy—A Review - Michał Kowalski; Adam Przybyłkowski (Diagnostics)
Background: Endoscopic retrograde cholangiopancreatography (ERCP) is a key therapeutic procedure in diseases of the pancreas or bile ducts. The understanding and effective management of the risks associated with the procedure, especially in the context of possible infectious complications, is crucial for patients’ safety. The aim of this review was to analyze the results of studies on antibiotic prophylaxis for infectious complications of ERCP, pancreatoscopy, and cholangioscopy. Methods: This study is a review of the articles available in PubMed, Medline, and Embase published in the last 30 years. Results: Nineteen studies and six sets of guidelines on antibiotic prophylaxis before ERCP were retrieved. Conclusions: Based on the available studies and recommendations, it can be concluded that antibiotic prophylaxis before ERCP is beneficial for immunocompromised patients or those at risk of bacterial endocarditis. In other groups of patients, antibiotic prophylaxis reduces the risk post-ERCP bacteremia but does not significantly reduce the risk of cholangitis and infectious complications. The effectiveness of antibiotic prophylaxis in patients at risk of incomplete biliary drainage needs to be verified in further studies.